Prácticas de consumo y estilo de vida de la población LGTB* de Bogotá** (2010)
This study corresponds to a trans-sectional non-experimental design with descriptive levels of analysis, comparison and correlation of the subgroups of the LGBT population and the heterosexual population resident in the city of Bogota-Colombia. A survey was constructed and applied to 639 people from the LGBT community and heterosexual in order to identify the practices of consumption (expenditure pattern of housing, utilities, home, etc.) and lifestyle (sporting and recreational among others). The results show that there are differences in lifestyle between LGBT groups and between it and heterosexuals. However, these differences are specific and not attributable solely to sexual orientation. In regard to consumption practices found that there are many more similarities than differences between women and gay men compared with their heterosexual counterparts, indicating that consumption is more associated with type of demographic variables to sexual orientation as such.